2018
DOI: 10.3329/dujps.v17i1.37120
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Anogeissus leiocarpus Guill and Perr Leaf on Hyperglycaemia and Associated Dyslipidaemia in Alloxan-induced Diabetic Rats

Abstract: People living with diabetes mellitus across the world are expected to rise to 592 million by 2035 and the pandemic disease is worst in the developing countries like Nigeria, where the cost of treating/managing diabetes mellitus is relatively out of the reach of many diabetic patients. The study investigated the effect of Anogeissus leiocarpus Guill and Perr ethanolic leaf extract on blood glucose and other biochemical indices in alloxan-induced diabetic adult male Wistar albino rats. Diabetes mellitus was indu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 20 publications
0
1
0
Order By: Relevance
“…This triglycerides level was reduced significantly in the liver of groups treated with total extract and supernatant. The in vivo potential antihyperlipidemic was also found by [ 26 ] on the leaves of Anogeissus leiocarpus on diabetic model of rats. The antihyperlipidemic activity of the total extract and especially supernatant may be due to the enhance of triglycerides catabolism.…”
Section: Discussionmentioning
confidence: 53%
“…This triglycerides level was reduced significantly in the liver of groups treated with total extract and supernatant. The in vivo potential antihyperlipidemic was also found by [ 26 ] on the leaves of Anogeissus leiocarpus on diabetic model of rats. The antihyperlipidemic activity of the total extract and especially supernatant may be due to the enhance of triglycerides catabolism.…”
Section: Discussionmentioning
confidence: 53%
“…The latter accelerated healing of surgically-induced deep skin wounds in alloxan-induced diabetic dogs 7 showing landmarks of enhanced inflammatory responses of healing processes 7 . The guill and perr leaf of A. leiocarpus were effective on the hyperglycaemia and the associated dyslipidaemia in alloxan-induced diabetic rats 12 while total extract and fractions exhibited antihyperglycaemic activity in mice 13 . The attenuation of dyslipidaemia on alloxan-induced diabetic dogs 6 and rats 12 by crude ethanolic extracts of A. leiocarpus is very important, laudable and requires more attention, since different classes of glucose lowering drugs, such as sulfonyl urea and meglitnides biguanides and thiazoliniediones 14,15 controlled the hyperglycaemia but did not effectively control the hyperlipidaemia associated with the DM, apart from the toxicity and resistance some patients experienced 16 and the exorbitant costs 17,18 for developing countries.…”
Section: Introductionmentioning
confidence: 98%
“…The guill and perr leaf of A. leiocarpus were effective on the hyperglycaemia and the associated dyslipidaemia in alloxan-induced diabetic rats 12 while total extract and fractions exhibited antihyperglycaemic activity in mice 13 . The attenuation of dyslipidaemia on alloxan-induced diabetic dogs 6 and rats 12 by crude ethanolic extracts of A. leiocarpus is very important, laudable and requires more attention, since different classes of glucose lowering drugs, such as sulfonyl urea and meglitnides biguanides and thiazoliniediones 14,15 controlled the hyperglycaemia but did not effectively control the hyperlipidaemia associated with the DM, apart from the toxicity and resistance some patients experienced 16 and the exorbitant costs 17,18 for developing countries. Due to the above-listed endowed medicinal activities and properties of A. leiocarpus, under the context of a nonconventional treatment for DM, the ethanolic extract of its stem bark was purified to the point of crystallization and four components, an interface and three fractions were produced 19 and the interface had a much higher proportion than the three other fractions 19 .…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Previous studies on roots, stem barks of the plant, revealed antimicrobial, antiproliferative, antioxidant and hepatoprotective properties 5,6,7 . The leaves of A. leiocarpus have been scientifically reported to decrease blood glucose effects in alloxan-induced diabetic rats 8 . Roots of this plant were also reported by Kpodar et al to be used traditionally to treat people living with diabetes in Togo 9 .…”
Section: Introductionmentioning
confidence: 99%